TWIX: Balancing Fairness and Utility in Item Exposure for Recommendation Systems - M. Silva, Maria de Lourdes; Chaves, Iago C.; Mendonça, André L. C.; D. Neto, Eduardo R.; Machado, Javam de Castro (Anais do Simpósio Brasileiro de Banco de Dados (SBBD); 2025: Anais do XL Simpósio Brasileiro de Bancos de Dados, 2025)
Recommendation systems personalize user experiences but often introduce the “rich-get-richer” effect, where popular items dominate visibility. This bias disadvantages new items or those with few interactions, where historical data limits the exposure of new items. To address these challenges, fairness in exposure has been studied through balanced exposure, which ensures equal visibility but may reduce recommendation utility, and quality-weighted exposure, which prioritizes high-quality items. To mitigate the trade-off between fairness and utility, we propose TWIX, a method that applies quality-weighted and balanced exposures determined by a threshold. Our approach reduces popularity bias and cold start issues while maintaining recommendation utility.